2001
DOI: 10.1093/nar/29.8.1781
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient base excision repair (BER) in human and rat male germ cells

Abstract: The quality of germ cell DNA is critical for the fate of the offspring, yet there is limited knowledge of the DNA repair capabilities of such cells. One of the main DNA repair pathways is base excision repair (BER) which is initiated by DNA glycosylases that excise damaged bases, followed by incision of the generated abasic (AP) sites. We have studied human and rat methylpurine-DNA glycosylase (MPG), uracil-DNA glycosylase (UNG), and the major AP endonuclease (HAP1/APEX) in male germ cells. Enzymatic activitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(48 citation statements)
references
References 68 publications
1
47
0
Order By: Relevance
“…Western blot analyses have supported the RNA data showing greater levels of DNA ligases I and III, Xrcc-1, Ape/Ref-1, and ␤-pol proteins in mixed germ cell (MGC, i.e., all spermatogenic cell types in adult testis) nuclear extracts than in adult somatic tissues (26,48). Furthermore, we have reported higher levels of uracil-DNA glycosylase-initiated base excision repair (UDG-BER) activity in MGC nuclear extracts obtained from young adult mice compared to extracts from brain, liver, enriched preparations of prepubertal Sertoli cells, thymocytes, and small intestine (26).…”
mentioning
confidence: 74%
“…Western blot analyses have supported the RNA data showing greater levels of DNA ligases I and III, Xrcc-1, Ape/Ref-1, and ␤-pol proteins in mixed germ cell (MGC, i.e., all spermatogenic cell types in adult testis) nuclear extracts than in adult somatic tissues (26,48). Furthermore, we have reported higher levels of uracil-DNA glycosylase-initiated base excision repair (UDG-BER) activity in MGC nuclear extracts obtained from young adult mice compared to extracts from brain, liver, enriched preparations of prepubertal Sertoli cells, thymocytes, and small intestine (26).…”
mentioning
confidence: 74%
“…However, recent reports (65) have indicated that nuclear DNA of human spermatozoa is relatively resistant to damage induced by H 2 O 2 and iron treatment in vitro. This particular paradox may be due to the high relative level of BER found in testes (53,54,66) and the ability of APE to function both as a BER enzyme and as a redox regulatory molecule. Because BER may function independently of APE (67), it is likely that under circumstances of FIG.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from the literature indicates that other DNA repair systems may play a role during spermiogenesis. Elements of the base excision repair (BER) have been identified in elongating and elongated spermatids [Olsen et al 2001]. In addition, there is evidence that mismatch repair (MMR) involving the MSH2 protein, is playing a role during spermiogenesis.…”
Section: Further Evidence Of a Dna Repair System In Spermatidsmentioning
confidence: 99%